Prognostic Impact of Baseline Liver Metastasis in ALK Fusion-Positive Metastatic Lung Cancer: A Retrospective Review - Khaddar, Satvik; Kapoor, Akhil; Noronha, Vanita; Patil, Vijay M.; Menon, Nandini; Mahajan, Abhishek; Janu, Amit; Kumar, Rajiv; Purandare, Nilendu; Prabhash, Kumar (South Asian Journal of Cancer, 2022)
Introduction The prognosis of anaplastic lymphoma kinase (ALK) fusion-positive metastatic non-small cell lung cancer (mNSCLC) patients has improved drastically since the introduction of targeted therapies. Apart from age, performance status, and type of driver mutation in a mNSCLC, prognosis also depends on baseline metastatic sites number as well as location with liver metastases being a poor prognostic factor. However, the clinical and prognostic association of baseline liver metastases in ALK fusion-positive mNSCLC is not well known.Material and Methods We performed a retrospective analysis of ALK fusion-positive mNSCLC patients to assess prognostic impact of liver metastases. Records were obtained from lung cancer audit database and electronic medical records. Patients were started on either chemotherapy, ALK-directed tyrosine kinase inhibitors, or given best supportive care as per the clinical scenario. Radiological response was assessed every 2 to 3 months or earlier at clinical suspicion of progressive disease. Adverse events were evaluated as per Common Terminology Criteria for Adverse Events v4.02.Results A total of 441 patients were screened, out of which 76 had baseline liver metastases. Median age was 49 years with 64.5% males. Median progression-free survival (mPFS) was 14.2 months (95% confidence interval [CI] 8.9–19.4) in patients with baseline liver metastases. In patients who received first-line ALK inhibitor therapy versus who received first-line chemotherapy, mPFS was significantly better in the ALK-directed therapy subgroup, 15.3 months (95% CI 11.7–18.9) versus 5.9 months (95% CI 2.7–9.1), respectively (hazard ratio [HR] 0.3 [95% CI 0.17–0.54]; p < 0.001). Median overall survival (mOS) was 27.6 months (95% CI 17.4–37.7) in patients with baseline liver metastases which was not statistically significant from patients without baseline liver metastases which was 32.3 months (95% CI 28.8–35.7) (HR 1.32 [95% CI 0.91–1.9]; p = 0.22). Use of ALK-directed therapy in patients with baseline liver metastases resulted in better OS, mOS not reached versus 15.7 months (95% CI 2.7–28.8) in the chemotherapy group (HR 0.33 [95% CI 0.16—0.67]; p < 0.001).Conclusion In patients with ALK fusion-positive mNSCLC, baseline liver metastases was not found to be an independent prognostic factor. However, the use of ALK-directed therapy resulted in a significantly better PFS and OS as compared with chemotherapy in patients with baseline liver metastases. This underscores the importance of the use of ALK-directed therapy whenever feasible in this group of patients.
Keywords: ALK; chemotherapy; crizotinib; liver metastases; NSCLC